Polymer surfaces graphitization by low-energy He+ ions irradiation - Geworski, Andreas; Lazareva, Irina; Gieb, Klaus; Koval, Yury; Müller, Paul (Journal of Applied Physics, 2014)
The electrical and optical properties of surfaces of polyimide and AZ5214e graphitized by low-energy (1 keV) He irradiation at different polymer temperatures were investigated. The conductivity of the graphitized layers can be controlled with the irradiation temperature within a broad range and can reach values up to ∼1000 S/cm. We show that the electrical transport in low-conducting samples is governed by thermally activated hopping, while the samples with a high conductivity show a typical semimetallic behavior. The transition from thermally activated to semimetallic conductance governed by the irradiation temperature could also be observed in optical measurements. The semimetallic samples show an unusually high for graphitic materials carrier concentration, which results in a high extinction coefficient in the visible light range. By analyzing the temperature dependence of the conductance of the semimetallic samples, we conclude that the scattering of charge carriers is dominated by Coulomb interactions and can be described by a weak localization model. The transition from a three to two dimensional transport mechanism at low temperatures consistently explains the change in the temperature dependence of the conductance by cooling, observed in experiments. © 2014 AIP Publishing LLC.